Trinculo: Bayesian and frequentist multinomial logistic regression for genome-wide association studies of multi-category phenotypes. - Jostins, L; McVean, G (Oxford University Press, 2016)
For many classes of disease the same genetic risk variants underly many related phenotypes or disease subtypes. Multinomial logistic regression provides an attractive framework to analyse multi-category phenotypes, and explore the genetic relationships between these phenotype categories. We introduce Trinculo, a program that implements a wide range of multinomial analyses in a single fast package that is designed to be easy to use by users of standard genome-wide association study software.An open source C++ implementation, with code and binaries for Linux and Mac OSX, is available for download at http://sourceforge.net/projects/trinculo/ CONTACT: lj4@well.ox.ac.uk.